Stiff Mutant Genes of Phycomyces Affect Turgor Pressure and Wall Mechanical Properties to Regulate Elongation Growth Rate - Ortega, Joseph K.; Munoz, Cindy M.; Blakley, Scott E.; Truong, Jason T.; Ortega, Elena L. (Frontiers in Plant Science, 2012)
Regulation of cell growth is paramount to all living organisms. In plants, algae and fungi, regulation of expansive growth of cells is required for development and morphogenesis. Also, many sensory responses of stage IVb sporangiophores of Phycomyces blakesleeanus are produced by regulating elongation growth rate (growth responses) and differential elongation growth rate (tropic responses). “Stiff” mutant sporangiophores exhibit diminished tropic responses and are found to be defective in at least four genes; madD, madE, madF and madG. Prior experimental research suggests that the defective genes affect growth regulation, but this was not verified. All the growth of the single-celled stalk of the stage IVb sporangiophore occurs in a short region termed the “growth zone”. Prior experimental and theoretical research indicates that elongation growth rate of the stage IVb sporangiophore can be regulated by controlling the cell wall mechanical properties within the growth zone and the magnitude of the turgor pressure. A quantitative biophysical model for elongation growth rate is required to elucidate the relationship between wall mechanical properties and turgor pressure during growth regulation. In this study, it is hypothesized that the mechanical properties of the wall within the growth zone of stiff mutant sporangiophores are different compared to wild type. A biophysical equation for elongation growth rate is derived for fungal and plant cells with a “growth zone”. Two strains of stiff mutants are studied, C149 madD120 (-) and C216 geo- (-). Experimental results demonstrate that turgor pressure is larger but irreversible deformation rates of the wall within the growth zone and growth zone length are smaller for stiff mutant sporangiophores compared to wild type. These findings explain the diminished tropic responses of the stiff mutant sporangiophores and suggest that the defective genes affect the amount of wall-building material delivered to the inner cell wall.